SAISMS : Transforming ammunition management through loT-enabled inventory and safety monitoring system - Mohammad Faris, Mahdhir; Nor Saradatul Akmar, Zulkifli; Mohd Zamri, Osman; Azlee, Zabidi; Mohd Izham, Mohd Jaya (Institute of Electrical and Electronics Engineers Inc., 2023)
Ammunition plays a crucial role in military and defense operations, requiring significant investments to arm military forces adequately. However, ammunition is susceptible to environmental factors that can degrade its quality, leading to defects or even accidental explosions. To ensure constant combat readiness, it is vital to maintain secure storage facilities with sufficient ammunition supplies. This project aims to enhance ammunition inventory and safety management procedures by leveraging loT technologies. This project proposed the implementation of an loT-powered web application dashboard that utilizes weight measurements to provide real-time inventory tracking and monitors environmental conditions such as temperature and humidity for quality control. Additionally, the system can predict ammunition condition outcomes. By adopting this loT-based solution, ammunition management processes will be streamlined, resulting in improved efficiency and effectiveness.